Characteristics and influence of home literacy environment in early childhood-centered literacy orientation - Sandra Sylvia Mascarenhas; Rajesh Moorakonda; Pratibha Agarwal; Sok Bee Lim; Sonoko Sensaki; Yap Seng Chong; John Carson Allen; Lourdes Mary Daniel (Proceedings of Singapore Healthcare, 2017)
Background: The home literacy environment (HLE) and joint parent–child book reading are key factors in children’s language and literacy acquisition. Child-centered literacy orientation (CCLO) refers to the child’s level of engagement in literacy events. Aim: To describe the HLE and identify demographic and HLE variables associated with a poor CCLO at 12 months of age. Methods: Parents of Singaporean children enrolled in the Growing Up in Singapore Towards healthy Outcomes (GUSTO; n = 1152, birth cohort 2009–2010) completed a childhood literacy questionnaire at 12 months to obtain scores on HLE (0–17) and CCLO (0–6). Logistic regression analyses were employed to identify predictors of low CCLO. Results: Parents of 525 children completed the questionnaire. Mothers were the main caregivers in half the households. Mandarin was the main language (34%). Majority of the respondents had a library card that was used less than weekly, and had fewer than 10 children’s books. 18% of parents read to the child daily, of whom one-quarter read at bedtime. Amongst half of the families who had a CCLO score of 0, two-thirds had the lowest HLE scores (0–2). Correlational analyses indicated significant association between HLE with CCLO at 12 months ( p < 0.001). Non-English speaking caregivers and mothers who had only completed primary education were at high risk of a poor 12-month CCLO. Conclusion: A literacy-rich home environment is associated with 12-month child-centered literacy orientation. Pediatricians and early years’ professionals may be able to promote benefits of literacy related activities to families at risk of poor child-centered literacy orientation.